Characteristics of lead-acid and nickel metal hydride batteries in uninterruptible power supply operation - Nurshahirah Athirah Rohman; Nor Farahaida Abdul Rahman; Muhammad Ammirrul Atiqi Mohd Zainuri (Institute of Advanced Engineering and Science, 2019)
Batteries are one of the main elements in Uninterruptable Power Supply (UPSs). To maintain good operation during power failure, UPSs must have adequate energy for their operation. It depends on the reliability and performance of batteries. Owing to low capital cost and wide availability, lead-acid batteries have been used extensively as the main energy source in UPSs. Nevertheless, as batteries technology grown, Nickel Metal Hydride (NiMH) batteries have offered more promising performance than lead-acid batteries; they are installed in various portable electronic devices. This paper provides an overview of the performance of lead-acid and NiMH batteries during the operation of a single-phase UPS. Their performances are studied based on 2 characteristics which are discharge curve and State of Charge (SOC). Based on those characteristics, both batteries have shown different performances. Simulation results have shown that the NiMH battery exhibits better discharge curve with higher voltage capacity and constant discharge current, and it is more reliable to obtain 12V at minimum percentage of SOC than the lead-acid battery.